Competitive Hill-Climbing Strategies for Replica Placement in a Distributed File System - Douceur, John (JD); Wattenhofer, Roger P. (Proceedings of 15th International Symposium on Distributed Computing (DISC), 2001)
The Farsite distributed file system stores multiple replicas of files on multiple machines, to provide file access even when some machines are unavailable. Farsite assigns file replicas to machines so as to maximally exploit the different degrees of availability of different machines, given an allowable replication factor R. We use competitive analysis and simulation to study the performance of three candidate hill-climbing replica placement strategies, MinMax, MinRand, and RandRand, each of which successively exchanges the locations of two file replicas. We show that the MinRand and RandRand strategies are perfectly competitive for R = 2 and 2/3-competitive for R = 3. For general R, MinRand is at least 1/2-competitive and RandRand is at least 10/17-competitive. The MinMax strategy is not competitive. Simulation results show better performance than the theoretic worst-case bounds.